Assessing harvesting and postharvest handling practices of Strychnos cocculoides fruit in the Kavango West Region of Namibia - Elago, Selma Ndemutila (Stellenbosch : Stellenbosch University, 2016)
Thesis (MScFor)--Stellenbosch University, 2016.